Achievement of LDL-Cholesterol Goals in Patients Receiving LLT in Primary Care: TERESA-AP Study - Sergio Cinza-Sanjurjo; Vivencio Barrios; David Fierro-González; Jose Polo-García; Vicente Pallarés-Carratalá (Cardiovascular Therapeutics)
Conclusions: On average, only a quarter of the patients followed up in PC and who receive drug treatment reach their therapeutic targets. This percentage is slightly higher if the patients have CVD and DM and lower if they have CKD. The most commonly used therapeutic strategy is moderate-intensity statins, both in monotherapy and in combination with ezetimibe.